A Quaternary Nitronyl Nitroxide α‐Amino Acid: Synthesis, Configurational and Conformational Assignments, and Physicochemical Properties. Issue 8 (14th January 2014) - Wright, Karen; d'Aboville, Edouard; Scola, Joseph; Margola, Tommaso; Toffoletti, Antonio; De Zotti, Marta; Crisma, Marco; Formaggio, Fernando; Toniolo, Claudio
Abstract: To expand the presently extremely limited repertoire of known nitronyl nitroxide α‐amino acids, we report here the synthesis of a novel, conformationally constrained, quaternary, chiral residue, Aic(CN), and its subsequent conversion into a blue‐colored, imidazolinyl nitronyl nitroxide‐bearing α‐amino acid, Aic(NN). Deprotection and peptide coupling reactions were examined. The configurational assignment of Aic(NN) was achieved by X‐ray crystallographic analysis of an appropriate tripeptide. This latter investigation, accompanied by an IR absorption conformational analysis, strongly supports the view that the Aic(NN) residue is an efficient peptide turn former. Numerous spectroscopic and magnetic properties of its derivatives and the tripeptide are also described. Of particular relevance for future applications are its UV/Vis absorption, NMR, and EPR signatures. Abstract : A blue, constrained α‐amino acid bearing a sidechain imidazolinyl nitronyl nitroxide was synthesized and its spectroscopic and magnetic properties were studied. It is foreseen that this turn‐supporting residue will prove to be useful as a rigid, paramagnetic probe in peptide chemistry.